Proceedings of the International Conference on Teacher Training and Education 2017 (ICTTE 2017) 2017
DOI: 10.2991/ictte-17.2017.92
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Teachers' Performance Based on Group of Age in Implementing Learning Process in Central Kalimantan

Abstract: The quality learning process can not be separated from the role of teachers as an educator. The Older teachers can be seen with their commitment to students. Younger teachers usually cultivate students' curiosity and interest in learning. Teachers recognize and try to fulfill their responsibilities to their students. This study aims to evaluate the performance of elementary school teachers by age group in implementing the learning process. This evaluation research used the 360 Degree Performance Appraisal Mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Table 3 shows the level of teaching performance of the Physics teachers, where This runs contrary to Bungai and Perdana [26] who cited some studies showing that the different age groups display dissimilar performance at work, where those who are both in their late ages tend to perform better.…”
Section: Level Of Teaching Performance Of Physics Teachersmentioning
confidence: 71%
“…Table 3 shows the level of teaching performance of the Physics teachers, where This runs contrary to Bungai and Perdana [26] who cited some studies showing that the different age groups display dissimilar performance at work, where those who are both in their late ages tend to perform better.…”
Section: Level Of Teaching Performance Of Physics Teachersmentioning
confidence: 71%
“…Previous research found that feedback on the measurement of lecturer performance has a positive effect on improving behavior in work that will impact performance by using the evaluation of the lecturer 360 Degree Performance Model. (Bungai & Perdana, 2017). Assessment of performance or also known as performance is a significant activity.…”
Section: Introductionmentioning
confidence: 99%